Kinematics of auto variator drive machines - P. D. Balakin; V. N. Belkov; A. V. Borodin (Омский научный вестник)
On the basis of theoretical provisions of the principle of design of mechanical systems by endowment of systems with properties of adaptation to real parameters and the operating mode it is offered to use for the control movement of energy of the main power flow and separate modeling of partial movement in a multi-mobile nonholonomic communication that allows to solve a problem of movement of mechanical system as a whole. For example, a frontal auto variator the decision communicated to the engineering calculation of the elements of the control circuit transfer function of auto variator under variable external loading.